Cultural Hybridity in African Diasporic and Immigrant Identities in Yaa Gyasi's Homegoing and Chimamanda Ngozi Adichie's Americanah - KASAP, ÖZGE NUR (İstanbul Kültür Üniversitesi, 2025)
This thesis analyzes the variation of cultural identity and its flexible nature in relation to the experiences of African Americans, African natives, and African immigrants, emphasizing the evolved historical and cultural distinction between them over time such as their perceptions of racism and the significance it holds for each group. In addition to acknowledging and addressing these differences, the thesis aims to examine the ideological movement of the 2000s, Afropolitanism, which encourages the embrace of culturally hybrid identities by introducing a fresh perspective to a globalized world where cultural identity is in constant flux. In this context, Yaa Gyasi's Homegoing and Chimamanda Ngozi Adichie's Americanah embody these arguments within their respective narratives. Yaa Gyasi's exploration of the interconnected histories of African and African American identities, formed by the impacts of colonialism and the transatlantic slave trade, provides the historical background that supports the arguments presented. Homegoing follows the pattern of these transformations in the span of seven generations through the narrative of two half-sisters: Effia, who experiences life under Western colonization in Ghana, and Esi, who suffers the brutality of slavery and its legacy in America. Framed through an Afropolitanist perspective, the novel highlights the dynamic and evolving nature of these identities across future generations, culminating in a globalized context by the novel's end. Chimamanda Ngozi Adichie's Americanah is the second key source for this thesis, offering an exploration of the lives of Nigerian immigrants and their efforts to balance the blending of cultures within the African diaspora, particularly in the USA. The novel examines the experiences of characters like Ifemelu, Uju, and Dike, highlighting their struggles to reconcile the traditional values of their African heritage with the contemporary influences of their new environment. Additionally, Adichie addresses the discord between African Americans and African immigrants, rooted in cultural differences that are often neglected by white American society. This thesis aims to analyze Adichie's illustration of fluid cultural identity, paralleling Gyasi's themes in Homegoing, and its connection to a wider discussion of cultural hybridity and global interrelation in Americanah.
Keywords: Postcolonial; African American; African Immigration; Cultural Hybridity; Afropolitanism; Chimamanda Ngozi Adichie; Americanah; Yaa Gyasi; Homegoing